Contribution of Agroforestry Systems to Farmer Income in State Forest Areas: A Case Study of Parungpanjang, Indonesia - Desmiwati, Desmiwati; Veriasa, Thomas Oni; Aminah, Aam; Safitri, Anggi Dian; Wisudayati, Tri Astuti; Hendarto, Kresno Agus; Royani, Hasan; Dewi, Kurniawati Hastuti; Raharjo, Sandy Nur Ikfal; Sari, Dian Ratna (Forest and Society, 2021)
Agroforestry activities in Forest Areas with Special Purpose (FASP) have been implemented since 2000 in Parungpanjang, West Java, which was subsequently reinforced by the Decree of the Minister of Environment and Forestry concerning the Recognition and Protection of Forest Partnerships (Kulin KK) for the Harapan Sejahtera and Guna Bakti Forest Farmer Groups in 2019. This study investigates the contribution of agroforestry systems to farmer income using a household survey in the Parungpanjang Research Forest. The study aims to analyze: 1) the contribution of agroforestry to farmer income from a household structured income analysis; 2) factors of agroforestry that influence total farmer household income using multiple regression analysis. The results show that agroforestry systems contributed 15.8% to farmer household income. The highest agroforestry productivity occurs in the age group of 41-45 years with an average of ​​managed land area of 0.65 hectares and average annual income of IDR 16,780,000 (USD 1,198.6)/farmer/year. The statistical model showed that agroforestry income does not have a significant influence on total farmer household income due to differences in the types of commercial crops, motivation, and skill, as well as age related to physical abilities.  There are only two agroforestry factors, namely age and land area, that have a significant influence on total farmer income, whereby the direction of the age variable has a negative influence.